(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of predication, a cornerstone of linguistic structure, by categorizing it into primary and secondary types. Primary predication is identified as the essential subject-predicate relationship that forms the foundation of any clause, such as in She is singing. Secondary predication, on the other hand, serves to complement or elaborate on the main clause, providing additional descriptive, resultative, or circumstantial details, as seen in She entered the room exhausted. The article delves into the syntactic and semantic roles of both types, emphasizing how primary predication establishes the core meaning, while secondary predication enriches sentences with supplementary layers of context. It also examines variations in non-finite constructions, cross-linguistic expressions, and theoretical perspectives, such as those offered by generative and functional grammar. Practical examples and distinctions between depictive and resultative secondary predicates are highlighted to illustrate their functions. Additionally, the article touches on the pedagogical significance of teaching these concepts, the cognitive processing of predication, and challenges like ambiguity in interpretation. Overall, this piece provides a comprehensive analysis of how predication structures enable nuanced and dynamic communication across languages and contexts.